2009
DOI: 10.4062/biomolther.2009.17.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Oxidantive Effect of Dehydroepiandrosterone on Indomethacin-Induced Acute Gastritis in Rats

Abstract: -This study examined whether or not a pretreatment with dehydroepiandrosterone (DHEA) has an effect on indomethacin-induced gastric mucosal damage. The DHEA group, male Sprague-Dawley rats, was administrated with DHEA orally at a dose of 4 mg/day for one week before inducing gastritis with indomethacin (50 mg/kg, p.o.). Histological assay, lipid peroxidation assay, superoxide dismutase (SOD), glutathione peroxidase (GPx) and Catalase activities were determined. Interestingly, it was found that the DHEA pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies reported that DHEA had antioxidant effects in various acute and chronic oxidative stress experiments (Jacob et al, ; Savineau, Marthan, & Dumas, ; Schwartz & Pashko, ). While, the effects of DHEA administration can be antioxidant (Jacob et al, ) or pro‐oxidant (Kim et al, ; Mastrocola et al, ) depending on the administered dose and specific tissue (Pélissier et al, ). Gallo et al () and Mastrocola et al () reported that slightly higher concentrations of DHEA protected cells against lipid peroxidation induced by oxidative stress, while at pharmacological doses, DHEA displayed a pro‐oxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that DHEA had antioxidant effects in various acute and chronic oxidative stress experiments (Jacob et al, ; Savineau, Marthan, & Dumas, ; Schwartz & Pashko, ). While, the effects of DHEA administration can be antioxidant (Jacob et al, ) or pro‐oxidant (Kim et al, ; Mastrocola et al, ) depending on the administered dose and specific tissue (Pélissier et al, ). Gallo et al () and Mastrocola et al () reported that slightly higher concentrations of DHEA protected cells against lipid peroxidation induced by oxidative stress, while at pharmacological doses, DHEA displayed a pro‐oxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of liver disease increases with age and older individuals are more susceptible to most acquired liver disorders (Huang, Hu, & Bao, ), and which may be related to the imbalance of oxidative homeostasis. Previous studies reported that DHEA exhibited antioxidant (Jacob, Janner, Bellóklein, Llesuy, & Ribeiro, ; Jacob et al, ) or pro‐oxidant effects (Kim et al, ; Mastrocola et al, ), and the modulatory functions depending on the dose administered and specific tissue (Gallo et al, ; Pélissier, Muller, Hill, & Morfin, ). Gallo et al () reported that slightly higher concentrations of DHEA protected cells against lipid peroxidation induced by oxidative stress, while DHEA displayed a pro‐oxidant activity at pharmacological doses.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a critical endogenous antioxidant and pro-oxidant activity. It can also protect against cell membrane lipid peroxidation (LPO) induced by oxidative damage 6 . DHEA also has anti-inflammatory properties via suppression of pro-inflammatory cytokines secretion like IL and TNF-α and regulating the body's immune response 7 .…”
Section: Introductionmentioning
confidence: 99%